Andrographolide is an Alternative Treatment to Overcome Resistance in ER-Positive Breast Cancer via Cholesterol Biosynthesis Pathway - Rajaratinam, Harishini (Malays J Med Sci, 2019)
Oestrogen receptor (ER)-positive breast cancer is one of the common forms of breast cancer affecting women worldwide. ER-positive breast cancer patients are subjected to anti-oestrogen therapy such as selective oestrogen receptor modulator (SERM) and aromatase inhibitors (AIs). Recently, the emergence of resistance to anti-oestrogen treatment is under intensive focus. The different mechanisms postulated to explain the occurrence of resistance in ER-positive breast cancer treatment include the loss of ER function and the crosstalk between signalling pathways in cancer cells. Recent literature highlighted that the cholesterol biosynthesis pathway acts as a novel mechanism underlying resistance to oestrogen deprivation. The present study aimed to highlight the role of cholesterol biosynthesis in anti-oestrogen treatment resistance, putatively suggesting an alternative plant-based treatment using andrographolide from Andrographis paniculata. The hypolipidaemic effect of andrographolide can be utilised to prevent the resistance in the treatment of ER-positive breast cancer contributed by cholesterol biosynthesis.